2015
DOI: 10.1080/01436597.2015.1038339
|View full text |Cite
|
Sign up to set email alerts
|

Aid and state transition in Ghana and South Korea

Abstract: This paper examines the questions of why and how foreign assistance was utilised successfully in South Korea but less so in Ghana, with a focus on the role of aid in the process of state building and state transition in these two countries. As multiple policy makers and scholars have noted, in 1957 South Korea and Ghana shared similar levels of GDP per capita, yet South Korea then achieved rapid economic development and democracy in one generation, while Ghana suffered from slow development and a general deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The central argument here is that corporate-driven community development endeavours-even if motivated by the best intentions-may keep communities in dependency, rather than empowering them through capacity-building and real participation. This argument resembles somewhat the foreign aid debate that underlines (for example in the case of the transition of South Korea) that the key factor of successful development was internal political processes that minimized negative side-effects of development aid, rather than direct external interventions in state-building (Kim, 2015). In the case of community involvement in a developing country context, it seems of outstanding importance to adopt a "community centred approach" (Misener and Mason, 2010) where communities have the power and control over decision-making and governance processes so to avoid currently widespread "hollow participation" (McCarthy and Muthuri, 2016;Mellahi and Wood, 2003) and allow for emancipation of the communities from corporate tutelage (McEwan et al, 2017).…”
Section: Corporate Community Involvement and Developmentmentioning
confidence: 79%
“…The central argument here is that corporate-driven community development endeavours-even if motivated by the best intentions-may keep communities in dependency, rather than empowering them through capacity-building and real participation. This argument resembles somewhat the foreign aid debate that underlines (for example in the case of the transition of South Korea) that the key factor of successful development was internal political processes that minimized negative side-effects of development aid, rather than direct external interventions in state-building (Kim, 2015). In the case of community involvement in a developing country context, it seems of outstanding importance to adopt a "community centred approach" (Misener and Mason, 2010) where communities have the power and control over decision-making and governance processes so to avoid currently widespread "hollow participation" (McCarthy and Muthuri, 2016;Mellahi and Wood, 2003) and allow for emancipation of the communities from corporate tutelage (McEwan et al, 2017).…”
Section: Corporate Community Involvement and Developmentmentioning
confidence: 79%
“…This has motivated some scholars as well as policy makers to search for plausible explanations. They include the publications of Werlin, (1991;1994;Kalu and Kim, 2014;Afesorgbor, 2014;Kim, 2015). For instance, Werlin in his 1991 publication pointed out that even though Ghana and South Korea had about the same annual per capita gdp in 1960, the latter's annual purchasing power per head was about ten times that of the former.…”
Section: The Comparative Literature On Ghana-korea Relationsmentioning
confidence: 99%
“…Under Rawlings, the country implemented Structural Adjustment Programmes (saps) have been widely imposed as a form of aid conditionality from 1984. The saps led to liberalisation of the external trade and financial sector regimes, the phasing out of price controls, measures to improve the financial performance of many stateowned enterprises, and the introduction of more competition (Kim, 2015). It also led to the stabilisation of prices, mainly through balanced budgets, market liberalisation, and public sector reform, all of which were aimed at creating a market-friendly environment (Tsikata, 2001).…”
Section: The Comparative Literature On Ghana-korea Relationsmentioning
confidence: 99%
“…The previous research on foreign aid and growth can be categorized into two separate parts. The empirical findings of some researcher showed that foreign aid accelerates financial growth (Kim, 2017). Others do not support this view (Mallik 2008;Herzer & Morrissey, 2013).…”
Section: Introductionmentioning
confidence: 99%